2018
DOI: 10.1021/acs.biomac.8b00402
|View full text |Cite
|
Sign up to set email alerts
|

Production and Properties of Triple Chimeric Spidroins

Abstract: All spider silk proteins (spidroins) are composed of N- and C-terminal domains (NT and CT) that act as regulators of silk solubility and assembly and a central repetitive region, which confers mechanical properties to the fiber. Among the seven types of spider silks, aciniform silk has the highest toughness. Herein, we fused NT and CT domains from major and minor ampullate spidroins (MaSps and MiSps), respectively, to 1-4 repeat domains (W) from another type of spidroin, aciniform spidroin 1(AcSp1). Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 54 publications
8
64
0
Order By: Relevance
“…The iN1RC spidroin showed the highest yield, i.e., 254 mg per liter shake flask culture, while that of iN4RC was 89 mg/L. By concentrating in 20 mM Tris buffer at pH 8.0, the solubility of the iNnRC spidroins showed a negative correlation to protein size (Table 1), in other words, with increasing repetitive unit R, the solubility of the spidroins gradually declined from more than 500 mg/mL for The yield of the iNnRC spidroins was negatively correlated to the protein molecular weight (Table 1), which is in line with previous reports on the productivity of recombinant spidroins [19,21]. The iN1RC spidroin showed the highest yield, i.e., 254 mg per liter shake flask culture, while that of iN4RC was 89 mg/L.…”
Section: Spidroin Production and Solubilitysupporting
confidence: 90%
See 4 more Smart Citations
“…The iN1RC spidroin showed the highest yield, i.e., 254 mg per liter shake flask culture, while that of iN4RC was 89 mg/L. By concentrating in 20 mM Tris buffer at pH 8.0, the solubility of the iNnRC spidroins showed a negative correlation to protein size (Table 1), in other words, with increasing repetitive unit R, the solubility of the spidroins gradually declined from more than 500 mg/mL for The yield of the iNnRC spidroins was negatively correlated to the protein molecular weight (Table 1), which is in line with previous reports on the productivity of recombinant spidroins [19,21]. The iN1RC spidroin showed the highest yield, i.e., 254 mg per liter shake flask culture, while that of iN4RC was 89 mg/L.…”
Section: Spidroin Production and Solubilitysupporting
confidence: 90%
“…The SDS-PAGE analysis (Figure 1a) showed that the purities of the four spidroins were all above 90%, and the result of western-blot ( Figure 1b) using anti-His-tag confirmed their identities. The yield of the iNnRC spidroins was negatively correlated to the protein molecular weight (Table 1), which is in line with previous reports on the productivity of recombinant spidroins [19,21]. The iN1RC spidroin showed the highest yield, i.e., 254 mg per liter shake flask culture, while that of iN4RC was 89 mg/L.…”
Section: Spidroin Production and Solubilitysupporting
confidence: 90%
See 3 more Smart Citations